SEISMIC STRATIGRAPHY ANALYSIS OF ABU FIELD, BLOCK PM 318, MALAY BASIN - ABDUL MALIK, MUHAMMAD HAZMI (2021)
A high resolution, 3D post-stack seismic survey from the Malay Basin has been acquired to build a 16.9 km x 15.8 km x 1.9 km [length x width x thickness] deterministic reservoir model which includes meandering channels, channels, and point bars. Identification of channel architecture and hydrocarbon potential undergo several analysis methods which include seismic interpretation, well log interpretation, attribute analysis, spectral decomposition, facies analysis and post-stack inversion. Physical attributes which are related to amplitude, frequency, phase and their derivative were used including variance, instantaneous frequency, sweetness and spectral decomposition. Seismic attributes controlled by well information demonstrated a good delineation of stratigraphic elements and lithological variations within the study area.